Odpowiedzi

2010-03-08T19:17:14+01:00
√3(2y + 3) - 3y(2 - √3) = 0
2√3 y + 3√3 - 6y + 3√3 y = 0
- 6y + 5√3 y = 3√3
y = 3√3/(5√3 - 6) = [3√3(5√3 + 6)]/(25*3 - 36) = [3√3(6 + 5√3)]/39 = √3(6 + 5√3)/13

2x(√2 + 1) = √2(3x - 7)
2√2 x + 2x = 3√2 x - 7√2
x(2 - √2) = - 7√2 |:√2
x(√2 - 1) = - 7
x = - 7/(√2 - 1) = - 7(√2 + 1)/(2 - 1) = - 7(√2 + 1)

2√5t - 5 = 3√5(8 - 7t) |:√5
2t - √5 = 24 - 21t
23t = 24 + √5
t = (24 + √5)/23

jak masz pytania to pisz na pw
2010-03-08T19:28:52+01:00
Rozwiąż równania:
√3(2y+3)-3y(2-√3)=0
2√3y+3√3-6y+3y√3=0
5√3y-6y=3√3
y(5√3-6)=3√3
y=3√3/(5√3-6)
y=3√3(5√3+6)/(5√3-6)(5√3+6)
y=3√3(5√3+6)/(75-36)
y=3√3(5√3+6)/(39)
y=√3(5√3+6)/13


2x(√2+1)=√2(3x-7)
2x√2+2x=3√2x-7√2
2x-1√2x=-7√2
x(2-1√2)=-7√2
x=-7√2/(2-1√2)
x=-7√2(2+1√2)/(2-1√2)(2+1√2)
x=-7√2(2+1√2)/(4-2)
x=-7√2(2+1√2)/2

2√5t-5=3√5(8-7t)
2√5t-5=24√5-21√5t
2√5t+21√5t=24√5+5
23√5t=24√5+5
t=(24√5+5)/23√5
t=(24√5+5)√5/23√5*√5
t=(120+5√5)/115